2007
DOI: 10.1111/j.1523-5378.2007.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrophic Gastritis, Helicobacter pylori, and Colorectal Cancer Risk: A Case‐Control Study

Abstract: Gastric conditions such as chronic H. pylori infection and atrophic gastritis are unlikely to increase the risk for CRC, although atrophic gastritis may increase the risk of rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 25 publications
0
56
3
Order By: Relevance
“…Several publications have reported that atrophic gastritis is not associated with increased CRC risk (25,26). Our study also found no statistically significant association in the risks of developing gastric atrophy in either the study or the control group (OR=1.24, p>0.05).…”
Section: Discussioncontrasting
confidence: 68%
“…Several publications have reported that atrophic gastritis is not associated with increased CRC risk (25,26). Our study also found no statistically significant association in the risks of developing gastric atrophy in either the study or the control group (OR=1.24, p>0.05).…”
Section: Discussioncontrasting
confidence: 68%
“…As for CAG, two reports have described non-significant results for the correlation between colorectal cancer and CAG (29,30). Our previous population-based case-control study comprising middle-aged male factory workers, which included adjustment for potential confounding factors, clearly demonstrated an increase in the risk of colorectal adenoma in the presence of H. pylori-associated chronic gastritis (7).…”
Section: Discussionmentioning
confidence: 75%
“…H. pylori in advanced gastric lesions has probably decreased because of migration through the gastrointestinal tract [55]. This suggests that with advanced gastric lesions, gastric lesions but not H. pylori status would be appropriate in the prediction of colorectal polyps [23,56,57]. Bulajic et al [24] found only 1.2% of malignant colorectal tissues were positive for H. pylori in contrast to 6% positive normal tissues from cancer patients.…”
Section: Discussionmentioning
confidence: 99%